Hemostatic properties and the role of cell receptor recognition in human hair keratin protein hydrogels - Burnett, Luke R.; Rahmany, Maria B.; Richter, Jillian R.; Aboushwareb, Tamer A.; Eberli, Daniel; Ward, Catherine L.; Orlando, Giuseppe; Hantgan, Roy R.; Van Dyke, Mark E. (Biomaterials, 2013)
Driven by new discoveries in stem-cell biology and regenerative medicine, there is broad interest in biomaterials that go beyond basic interactions with cells and tissues to actively direct and sustain cellular behavior. Keratin biomaterials have the potential to achieve these goals but have been inadequately described in terms of composition, structure, and cell-instructive characteristics. In this manuscript we describe and characterize a keratin-based biomaterial, demonstrate self-assembly of cross-linked hydrogels, investigate a cell-specific interaction that is dependent on the hydrogel structure and mediated by specific biomaterial–receptor interactions, and show one potential medical application that relies on receptor binding - the ability to achieve hemostasis in a lethal liver injury model. Keratin biomaterials represent a significant advance in biotechnology as they combine the compatibility of natural materials with the chemical flexibility of synthetic materials. These characteristics allow for a system that can be formulated into several varieties of cell-instructive biomaterials with potential uses in tissue engineering, regenerative medicine, drug and cell delivery, and trauma.